Nilai-nilai Islam dalam Kebudayaan Indonesia (Kajian Filsafat Nilai) - Widyastini Widyastini (Jurnal Filsafat "WISDOM", 2004)
Indonesia consisted of many islands tribes, customs, and traditions cultures, and several kinds of religion. Their diversity, line "zamrud khatulistiwa" and "mutu manikam" decorated Indonesian Archipelago, and God has granted to be given to Indonesian people. Indonesia as a nation which is daily life relied on divinity and humanity always strove for the attainment of implementing and understanding of religion tenet according to their belief and faith without any threat and complusion from others. Since Indonesia has existed and liberated, Bhinneka Tunggal Ika is a symbolization of Indonesia's intergrity and it is brought on unity to them. Most of Indonesians are moslems, then it is natural if their life can not be separated from Islamic values which pervaded and covered every part of life. This is kind of materialization that should be perpetuated.